Surgeon and Patient Upper Extremity Dominance Does Not Influence Clinical Outcomes After Total Shoulder Arthroplasty. Issue 7 (8th July 2020) - Berthold, Daniel P.; Muench, Lukas N.; Kia, Cameron; Ziegler, Connor G.; Laurencin, Samuel J.; Witmer, Daniel; Reed, Dale N.; Cote, Mark P.; Arciero, Robert A.; Mazzocca, Augustus D.
Background: Surgeon- and patient-specific characteristics as they pertain to total shoulder arthroplasty (TSA) are limited in the literature. The influence of surgeon upper extremity dominance in TSA and whether outcomes vary among patients undergoing right or left TSA with respect to surgeon handedness have yet to be investigated. Purpose: To determine whether surgeon or patient upper extremity dominance has an effect on clinical outcomes after primary TSA at short-term follow-up. Study Design: Case series; Level of evidence, 4. Methods: A retrospective chart review was performed on prospectively collected data from an institutional shoulder registry. Patients who underwent primary TSA for glenohumeral osteoarthritis from June 2008 to August 2012 were included in the study. Preoperative and postoperative American Shoulder and Elbow Surgeons (ASES), Simple Shoulder Test (SST), and visual analog scale (VAS) pain scores were evaluated. To determine the clinical relevance of ASES scores, the minimal clinically important difference (MCID), the substantial clinical benefit (SCB), and the patient acceptable symptom state (PASS) were used. Active forward elevation, abduction, and external rotation were recorded for each patient. Glenoid version was also evaluated preoperatively on standard radiographs. Results: Included in this study were 40 patients (n = 44 shoulders; mean age, 69.0 ± 7.3 years) with a mean follow-up of 36.5 ± 16.2 months. Final active range of motion between patients who underwent dominant versus nondominant and left versus right TSA by a right-handed surgeon was not significantly different. Clinical outcomes including the ASES, SST, and VAS pain scores were compared, and no statistical significance was identified between groups. With regard to the ASES score, 89% of patients achieved the MCID, 64% achieved the SCB, and 60% reached or exceeded the PASS. No significant difference in preoperative glenoid version between groups could be found. Conclusion: With the numbers available, neither patient nor surgeon upper extremity dominance had a significant influence on clinical outcomes after primary TSA at short-term follow-up. Clinical Relevance: The influence of surgeon and patient upper extremity dominance on TSA outcomes is an important consideration, given the preferential use of the dominant extremity exhibited by most patients during activities of daily living. To this, operating on a right shoulder might be technically more demanding for a right-handed surgeon and vice versa, as it is considered in other subspecialties.